Mannose: A Sweet Option in the Treatment of Cancer and Inflammation - Nan, Fang; Sun, Yutong; Liang, Hantian; Zhou, Jingyang; Ma, Xiao; Zhang, Dunfang (Frontiers in Pharmacology, 2022)
As a natural sugar, mannose is a type of hexose that is abundant in many different types of fruits. Since mannose is rarely used for glycolysis in mammals, studies on the role of mannose have not attracted much attention. Glycosylation of specific proteins was thought to be the major function of mannose. Surprisingly, during the past few years, mannose was found to be effective in promoting immune tolerance and suppressing inflammatory diseases related to autoimmunity and allergy. Moreover importantly, mannose was also found to be efficient in suppressing tumors by suppressing glycolysis and enhancing chemotherapeutic agents. In this review, we summarize the recent studies of mannose on antitumor properties and anti-inflammatory characteristics. We emphasize that mannose could play a beneficial role in the treatment of a variety of diseases, including cancers and inflammatory diseases, and could be a novel therapeutic strategy that deserves continued evaluation.